PERAMALAN JUMLAH KEBUTUHAN AIR BERSIH DENGAN DOUBLE EXPONENTIAL SMOOTHING ANALYSIS (STUDI KASUS UPT MA’HAD AL- JAMI’AH UIN RADEN INTAN LAMPUNG) - Puput Nurmawati; Achi Rinaldi; Tatang Julianto; Indah Resti Ayuni Suri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Adequate access to clean water is a crucial necessity, especially for students(mahasantri) residing at Ma’had al-Jami’ah, a Technical Implementation Unit(UPT) under UIN Raden Intan Lampung. The increasing number of residents,uncertainty in water availability, and limited water sources pose significantchallenges in fulfilling clean water needs optimally. Therefore, a quantitativeanalysis of clean water demand is essential to determine the daily supplyrequirements. This study aims to calculate the daily water needs and forecastfuture demands as a basis for more efficient planning. The research employs theExponential Smoothing method using R software. To assess forecasting accuracy,the indicators used include Mean Absolute Percentage Error (MAPE), MeanAbsolute Error (MAE), and Mean Squared Error (MSE). The findings indicate thatthe clean water requirement that must be fulfilled is approximately 0.5079liters/second/day. The forecasting error values obtained are MAPE at 28.9%, MSEat 0.01568777, and MAE at 3.893837, which indicate an acceptable level ofaccuracy. In conclusion, the need for clean water is directly proportional to thenumber of mahasantri residing in the facility. Therefore, the provision of cleanwater should be aligned with actual demand data to ensure a more organized andefficient distribution. This approach supports sustainable water management andcontributes to the overall comfort and health of the dormitory environment.